Defect passivation of transition metal dichalcogenides via a charge transfer van der Waals interface - Yuzheng Guo (Science Advances, 2017)
Integration of transition metal dichalcogenides (TMDs) into next-generation semiconductor platforms has been limited due to a lack of effective passivation techniques for defects in TMDs. The formation of an organic-inorganic van der Waals interface between a monolayer (ML) of titanyl phthalocyanine (TiOPc) and a ML of MoS2 is investigated as a defect passivation method. A strong negative charge transfer from MoS2 to TiOPc molecules is observed in scanning tunneling microscopy. As a result of the formation of a van der Waals interface, the ION/IOFF in back-gated MoS2 transistors increases by more than two orders of magnitude, whereas the degradation in the photoluminescence signal is suppressed. Density functional theory modeling reveals a van der Waals interaction that allows sufficient charge transfer to remove defect states in MoS2. The present organic-TMD interface is a model system to control the surface/interface states in TMDs by using charge transfer to a van der Waals bonded complex.